2012
DOI: 10.4103/0300-1652.104384
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of admission cardiotocography for intrapartum monitoring in low resource setting

Abstract: BackgroundTo evaluate the role of admission cardiotocography in intrapartum patients in detecting fetal hypoxia already present and to correlate the results of admission cardiotocography with perinatal outcome.Materials and Methods:It was a cross-sectional study conducted in the Labor and Maternity ward during the period 2007-2009. The study included 176 pregnant women (both high risk and low risk), admitted to the emergency department or through the outpatient department with period of gestation ≥36 weeks, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 12 publications
4
23
0
Order By: Relevance
“…Thus the above finding suggests that babies from reassuring CTG required less resuscitation and NICU admission. The findings were similar with the study done by Rahman et al 16 where incidences of NICU admission was significantly high in babies delivered from mother with ominous test group (62%) compared to those with equivocal test group (28%) and reactive test group (3.45%). In study by Sandhu et al 22 neonatal admission to NICU was required in 1% of cases with a reactive AT, 12% of cases with an equivocal AT and 33% of cases with an ominous AT (p<0.01).…”
Section: Figure 1: Admission Test Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Thus the above finding suggests that babies from reassuring CTG required less resuscitation and NICU admission. The findings were similar with the study done by Rahman et al 16 where incidences of NICU admission was significantly high in babies delivered from mother with ominous test group (62%) compared to those with equivocal test group (28%) and reactive test group (3.45%). In study by Sandhu et al 22 neonatal admission to NICU was required in 1% of cases with a reactive AT, 12% of cases with an equivocal AT and 33% of cases with an ominous AT (p<0.01).…”
Section: Figure 1: Admission Test Resultssupporting
confidence: 82%
“…In ominous AT group of 14 cases, 2(14.3%) had normal vaginal delivery, 11(78.6%) had LSCS and 1(7.1%) had instrumental delivery. The study by Rahman 16 showed that operative delivery for fetal distress was required in only 5.5% women of the reactive group, in 27.8% of equivocal group and in 84.6% of the ominous group. The low percentage of operative deliveries in reactive and equivocal groups may be because the cases with equivocal trace were placed on continuous CTG monitoring.…”
Section: Figure 1: Admission Test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In the study by Shreshtha P et al Cat.-I is 77%, Cat.-II 9%) and Cat.-III 20% while in the study by Rahman H et al; Cat.-I is 77.0%, Cat.-II 14%) and Cat.-III 9%. 18,19 Observation regarding color of liquor found to be comparable to studies by Becker S, where prevalence was 10%, Ziadeh SM et al also had prevalence of 11%, while Maymon E et al in the study had 17% prevalence and Nathan et al in their study had prevalence of 20%. [21][22][23] In the oligohydramnios (<5 cm) group, there was significant association with pathological NST at admission, meconium stained liquor during Labor, caesarean delivery for fetal distress, newborn APGAR at 1 minute <7, NICU admission and newborn mortality ('p' value <0.00001) ( Table 2).…”
Section: Discussionsupporting
confidence: 68%
“…In a similar study by Rahman H et al 19 Cat.-I had 11% intervention, Cat.-II had 39% needed intervention, and Cat.-III had 86% needed intervention (LSCS). In the study Sandhu et al, 15% intervention in Cat.-I NST 55% intervention in Cat.-II and 73% intervention in Cat.-III NST.…”
Section: Discussionmentioning
confidence: 93%